Reduced and standard field-of-view diffusion weighted imaging in patients with rectal cancer at 3 T: comparison of image quality and apparent diffusion coefficient measurements - Attenberger, Ulrike; Tavakoli, Andrej; Stocker, Daniel; Stieb, Sonja; Riesterer, Oliver; Turina, Matthias; Schönberg, Stefan; Pilz, Lothar R.; Reiner, Caecilia Sophie (European journal of radiology, 2020)
Purpose - To compare a zoomed EPI-DWI (z-EPI) with a standard EPI-DWI (s-EPI) in the primary diagnostics of rectal cancer and assess its potential of reduced image artifacts. - Method - 22 therapy-naïve patients with rectal cancer underwent rectal MRI at a 3 T-system. The protocols consisted of a z-EPI DWI and s-EPI DWI sequence. Images were assessed by two independent and experienced readers regarding overall image quality and artifacts on a 5-point Likert scale, as well as overall sequence preference. In a lesion-based analysis, tumor and lymph node detection were rated on a 4-point Likert scale. Apparent diffusion coefficient (ADC) measurements were performed. - Results - Overall Image quality score for z-EPI and s-EPI showed no statistically significant differences (p = 0.80/0.54, reader 1/2) with a median score of 4 (“good” image quality) for both sequences. The image quality preference rank for z-EPI and s-EPI was given the category ‘no preference’ in 64 % (reader 1) and 50 % (reader 2). Most artifact-related scores (susceptibility, motion and distortion) did not show reproducible significant differences between z-EPI and s-EPI. The two sequences exhibited comparable, mostly good and excellent quality scores for tumor and lymph node detection (p = 0.19−0.99). ADC values were significantly lower for z-EPI than for s-EPI (p = 0.001/0.002, reader 1/2) with good agreement of ADC measurements between both readers. - Conclusion - Our data showed comparable image quality and lesion detection for the z-EPI and the s-EPI sequence in MRI of rectal cancer, whereas the mean ADC of the tumor was significantly lower in z-EPI compared to s-EPI.
Online verfügbar: 6. September 2020
Gesehen am 23.06.2025